Is it reliable to assess visual attention of drivers affected by Parkinson's disease from the backseat?: A simulator study - Lee, Hoe; Chee, D.; Selander, H.; Falkmer, Torbjorn (Co-Action Publishing, 2012)
Background: Current methods of determining licence retainment or cancellation is through on-road driving tests. Previous research has shown that occupational therapists frequently assess drivers’ visual attention while sitting in the back seat on the opposite side of the driver. Since the eyes of the driver are not always visible, assessment by eye contact becomes problematic. Such procedural drawbacks may challenge validity and reliability of the visual attention assessments. In terms of correctly classified attention, the aim of the study was to establish the accuracy and the inter-rater reliability of driving assessments of visual attention from the back seat. Furthermore, by establishing eye contact between the assessor and the driver through an additional mirror on the wind screen, the present study aimed to establish how much such an intervention would enhance the accuracy of the visual attention assessment. Methods: Two drivers with Parkinson’s disease (PD) and six control drivers drove a fixed route in a driving simulator while wearing a head mounted eye tracker. The eye tracker data showed where the foveal visual attention actually was directed. These data were time stamped and compared with the simultaneous manual scoring of the visual attention of the drivers. In four of the drivers, one with Parkinson’s disease, a mirror on the wind screen was set up to arrange for eye contact between the driver and the assessor. Inter-rater reliability was performed with one of the Parkinson drivers driving, but without the mirror. Results: Without mirror, the overall accuracy was 56% when assessing the three control drivers and with mirror 83%. However, for the PD driver without mirror the accuracy was 94%, whereas for the PD driver with a mirror the accuracy was 90%. With respect to the inter-rater reliability, a 73% agreement was found.Conclusion: If the final outcome of a driving assessment is dependent on the subcategory of a protocol assessing visual attention, we suggest the use of an additional mirror to establish eye contact between the assessor and the driver. The clinicians’ observations on-road should not be a standalone assessment in driving assessments. Instead, eye trackers should be employed for further analyses and correlation in cases where there is doubt about a driver’s attention